LncRNA FGD5-AS1 Facilitates the Radioresistance of Breast Cancer Cells by Enhancing MACC1 Expression Through Competitively Sponging miR-497-5p - Li, Ji; Lei, Changjiang; Chen, Bineng; Zhu, Qingfang (Frontiers in Oncology, 2021)
LncRNA-FGD5-AS1, as an oncogene, participates in the development and progress of various cancers. However, the exact role and the molecular mechanisms by which FGD5-AS1 regulates radiosensitivity in breast cancer (BC) remains largely unknown. We used X-Ray weekly-dose-increase method to establish radiation-resistance cell lines. Bioinformatics tools analyze the expression of FGD5-AS1 in breast cancer tissue and evaluated the relationship between FGD5-AS1 and clinic-pathological features. CCK-8 and colony formation were used to analyze cell proliferation. Western blotting and qPCR were applied to detect protein and gene expression, respectively. RNA interference was used to knock down the endogenous gene expression. Luciferase reporter system and immunoprecipitates were applied to verify the target of FGD5-AS1. Result showed that FGD5-AS1 was overexpressed in BC tissues and radiation-resistance cell lines. Higher levels of FGD5-AS1 predicted poorer clinical characteristics and prognosis. Loss-of-function FGD5-AS1 sensitized BC cells to X-ray, meanwhile, the cell gained radiation-resistance when exogenous FGD5-AS1 was expressed. FGD5-AS1 depletion arrested cells at G0/G1 and triggers cell apoptosis. The starBase database (ENCORI), predicted binding site of miR-497-5p in FGD5-AS1 sequence, and luciferase reporter system and immunoprecipitates verified miR-497-5p was the target of FGD5-AS1. Furthermore, MACC1 was predicted and verified as the target of miR-497-5p. Loss-of-function FGD5-AS1 sensitized ionizing radiation was rescued by the up-regulation of MACC1 and the inhibition of miR-497. In conclusion, FGD5-AS1 displays an oncogene profile in CRC; patients with high expression of FGD5-AS1 should benefit less from radiotherapy and need a more frequent follow-up. Besides, FGD5-AS1 may be a potential therapeutic target for CRC.